Association between acute graft pyelonephritis and kidney graft survival: A single‐center observational study. Issue 11 (24th June 2021) - Maanaoui, Mehdi; Baes, Dulciane; Hamroun, Aghilès; Khedjat, Kahina; Vuotto, Fanny; Faure, Emmanuel; Lopez, Benjamin; Bouyé, Sébastien; Caes, Thomas; Lionet, Arnaud; Lebas, Céline; Provôt, François; et al.
Abstract : The association between acute graft pyelonephritis (AGPN) and graft failure in kidney transplant recipients (KTR) remains controversial. In this single‐center observational study, we aimed to assess the incidence of AGPN as a time‐dependent posttransplantation event. We also examined the association between the diagnosis of AGPN and graft outcomes. In total, we evaluated 1480 patients who underwent kidney transplantation between January 2007 and December 2017. During a median follow‐up of 5.04 years, we observed 297 AGPN episodes that occurred in 158 KTR. To evaluate the association between AGPN and clinical outcomes, we performed Cox proportional hazards regression analyses in which AGPN was entered as a time‐dependent covariate. AGPN was independently associated with an increased risk of graft loss (hazard ratio = 1.66; 95% confidence interval [CI]: 1.05−2.64, p < .03) and a persistently decreased eGFR (fixed effect on intercept: −2.29 ml/min/1.73 m 2 ; 95% CI: from −3.23 to −1.35, p < .01). However, neither mortality nor biopsy‐proven acute rejection was found to correlate with AGPN. Moreover, recurrent AGPN episodes did not appear to have an additive detrimental impact on graft loss. These data represent a promising step in understanding whether AGPN prevention may decrease the risk of graft loss in KTR. Abstract : A single‐center observational study shows that acute graft pyelonephritis in kidney transplant recipients is associated with allograft loss and a persistent decrease of allograft function.